Pendekatan Holistik Melalui Pendidikan Islam - Fahmi, Nurul (Al-Riwayah : Jurnal Kependidikan, 2017)
Development of the education system including the elements related to a positive pretense to the success of a holistic education looks when it is constructed in frame of education. But the present education system is in fact only preparing students for entry into university level, rather than developing the potential that he had been taken of each individual. Education system that can be framed pre-life of the human is a holistic education, the education that the substance contains the values that are universal and comprehensive management are managed by good management and completely so that the product will have the holistic education ability, not partial